Motif dan Kepuasan Anak Muda Kota Denpasar Menonton Live Instagram Bunda Corla - Marina, Gusti Putu Iangy; Suryawati, I Gusti Agung Alit; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2025)
Instagram is a photo and video based social media application that has plenty feature. One of the feature is Instagram live that lets the user live stream or broadcast to the followers in real-time. In consuming media, especially Instagram live, people using media based on a few motives. The aim of this research is to find out what is the underlying motives of  Denpasar’s youth to watch Bunda Corla’s Instagram Live and how satisfaction is obtained by watching Bunda Corla’s Instagram Live. This research using descriptive quantitative method with the subjects choosen is Denpasar’s youth aged 15-24 years. The theory used in this study is Uses and Gratifications theory with Denis McQuail’s motives concept which consist of four motives such as, information, personal identify, integration and social interaction, and entertaintment motives. The result of the reaserch showed that there are two motives that were satisfied, such as integration and interaction motive and also entertainment motive.   Keywords: Motives, Satisfaction, Youth, Denpasar, Instagram